PO 8194 Optimised informed consent for participants in a randomised controlled trial in rural uganda: a comparative prospective cohort study. (24th April 2019) - Ditai, James; Kanyago, Jesca; Nambozo, Rachael; Kanyago, Nathan; Abeso, Julian; Olupot, Peter; Carrol, Enitan; Gladstone, Melissa; Weeks, Andrew; Faragher, Brian; Medina-Lara, Antonietta; Storr, Julie
Abstract : Background: Poor participant understanding of research information can be a problem in community interventional studies in rural African women where levels of illiteracy, dependency and compliance are high. We assessed the impact of alternative consent models on participants' understanding of the clinical trial information and its contribution to the informed consent process in rural Uganda. Methods: This was a prospective comparative cohort, nested within a pilot study of community distribution of alcohol-based hand rub to prevent neonatal sepsis (BabyGel). As part of the informed consent process, information about the trial was presented using one of three consent methods: standard researcher-read information; a 'slide show' using illustrated text on a flip chart; and a video showing the patient information sheet (PIS) being read as if by a newsreader in either English or the local language. In addition, all women received a written PIS in their preferred language. Each information method was used for 1 week of recruitment. Two days after recruitment, women's understanding of the clinical trial was evaluated. Results: A total of 30 pregnant women from 13 villages in Mbale participated in this study. Majority 90% (27/30) were assessed for recall of trial information within planned 48 hours. The slide-show was the most popular, with a mean score not less than 4.2 highest [mean (sd) range: 4.8 (0.6) [4–5]] by women who had been recruited using any of the three models. The slide show was preferred by 63% of the women (19/30), compared with 17% (5/30) and 20% (6/30) who preferred the standard and video show message, respectively. Reasons given included the benefits of having pictures to aid understanding, and the logical progression of the information. Conclusion: Our results suggest that a slide-show message is an effective and popular alternative way of presenting trial information to women in rural Uganda, many of whom had little or no literacy.